(untitled) (Global Journal of Human-Social Science, 2012)
This paper examined the implications of Human Trafficking for Human Rights in Nigeria The henomenon of human trafficking has taken an alarming dimension in Nigeria such that it had become a big illegal criminal business Human trafficking is now a daily occurrence in Edo and Delta States of Nigeria Also the spread of human trafficking to other States of the country is believed to be the fallout of massive unemployment and high level of poverty Human trafficking is a major National problem for been a threat to fundamental human rights of the Nigerian citizenry For an already crestfallen nation the added burden of crime of human trafficking which are infringements on the fundamental human rights of Nigeria now transcend subliminal trauma For most parents in Nigeria the fear of sudden disappearances of their sons daughters and wards of being trafficker victims are real and palpable This paper examined the nature of human trafficking how does it affect the human rights of Nigerians and how to manage it with a view of preserving human rights in Nigeria It was discovered that human trafficking is a crime against humanity Recommendations were made on how it could be managed in order not to infringe on fundamental human rights of Nigerians